Do Pension Benefits Accelerate Cognitive Decline? Evidence from Rural China - Plamen Nikolov; Alan Adelman (Institute of Labor Economics (IZA), 2019)
Higher life expectancy and rapidly aging populations have led to the introduction of pension programs in developing countries in the last two decades. Using the introduction of a new public policy in China, we estimate the effects of pension benefits on individual cognition, measured by episodic memory and intact mental status, among individuals ages 60 and above. We find large and significant negative effects of the provision of pension benefits on cognitive functioning among the elderly. We find the largest effect of the program on delayed recall, a measure implicated in neurobiological research as an important predictor of the onset of dementia. We show that the program leads to more negative impacts among the female sample. Our findings support the mental retirement hypothesis that decreased mental activity results in atrophy of cognitive skills. We show that retirement plays a significant role in explaining cognitive decline at older ages.
Keywords: J14; H55; H75; J26; J24; D91; O12; N35; O10; 330; life-cycle; cognitive functioning; cognition; aging; health; mental retirement; middle-income countries; developing countries; China